2013
DOI: 10.1057/jdg.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, size and disclosure of related party transactions, and firm value: Indonesia evidence

Abstract: is a research fellow at FEUI. She is also a lecturer in the Bachelor and Master programs at FEUI. Her areas of interest include investment in capital markets, corporate finance and corporate governance. She has authored a number of articles and papers and has presented her research works in international as well as national conference/seminars. Sidharta Utamais a full professor at the University of Indonesia (UI) and is the chairman of the management board of the Indonesian Institute for Corporate Directorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 48 publications
5
29
1
12
Order By: Relevance
“…Most previous studies focused on investigating the effects of CG's moderation on RPT relationships with market reactions (Cheung et al (2006); Utama et al (2010); Ryngaert and Thomas (2012)) or company values (Kohlbeck and Mayhew (2010); Utama & Utama (2014); Elkelish (2017)). Koestaman and Diyanti (2013) have tested the effect of CG's moderation, but on the relationship between family ownership and cash dividend payouts.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies focused on investigating the effects of CG's moderation on RPT relationships with market reactions (Cheung et al (2006); Utama et al (2010); Ryngaert and Thomas (2012)) or company values (Kohlbeck and Mayhew (2010); Utama & Utama (2014); Elkelish (2017)). Koestaman and Diyanti (2013) have tested the effect of CG's moderation, but on the relationship between family ownership and cash dividend payouts.…”
Section: Introductionmentioning
confidence: 99%
“…One study shows that an exogenous increase in the proportion of independent directors results in an increase in corporate transparency (Armstrong et al 2014). A study in Indonesia also supports the argument that the quality of RPT disclosure typically means better corporate governance (Utama & Utama 2014). Another study confirms the effect in 26 Code of Corporate Governance 2012, Guideline 12.1 (Singapore).…”
Section: B Effect Of Board Independence On Tunnelingmentioning
confidence: 85%
“…Yeh et al find a negative correlation between better corporate governance and RPT in a study in Taiwan (Yeh et al ). Utama and Utama examine more than 200 firms listed in Indonesia with financial data between 2005 and 2008 and find that better corporate governance is negatively correlated with RPT liabilities, although they find no significant correlation with RPT assets (Utama & Utama ). Nonetheless, none of these studies identified the causal link between higher board independence and fewer RPTs.…”
Section: Legal Transplant Board Independence and Tunnelingmentioning
confidence: 99%
“…Regulation of the Capital Market and Financial Institution Supervisory Agency (BAPEPAM-LK) Number VIII.G.7 (2012), which regulates the presentation and disclosure of financial statements of issuers or public Advances in Social Science, Education and Humanities Research,volume 426 companies, specifies what components of financial statements should be disclosed in case of transactions with related parties (RPT). Previous research has summarized this rule and indicates that there are ten components of RPT to be disclosed by the company (Utama & Utama, 2014): (1) the amount of RPT in assets and liabilities;…”
Section: Transfer Pricing Regulations In Indonesiamentioning
confidence: 99%
“…Referring to the results of previous studies (Utama & Utama, 2014), this study measured RPTs based on the RPT disclosure group, the RPT associated with the asset group (RPTA) and the RPT associated with the liability group (RPTL). This study did not test the size of RPT based on sales (RPTS) and expenses (RPTE), because based on sample analysis, many companies do not disclose the value of RPTS and RPTE.…”
Section: Additional Testmentioning
confidence: 99%